Margaret’s recovery way in Jacqueline Woodson’s Last Summer with Maizon: father death and writing opportunity - Pratiwi, Rahmawati Hana; Sa'adah, Sufi Ikrima; Fanani, Abu (Universitas Mulawarman, 2024)
The study represents Margaret’s struggle to overcome the experience of grief in Last Summer with Maizon by Jacqueline Woodson. The study adopted a qualitative content analysis (QCA) approach to reveal the true meaning of the experience of grief, conveying a new interpretation of Margaret’s life, which is a way of recovering herself from grief. This approach also conducted the process of subjectivity by developing the quality of themes regarding Margaret’s grief struggle using the five phases of thematic analysis. The results of this study consist of discoveries and critical analysis regarding the issue of Margaret’s grief experience, which develops a sure way to get through it. The research findings section describes the initial signs leading up to the experience of grief faced by Margaret. Meanwhile, the critical analysis section describes the struggle to continue living without Margaret’s loved ones, the struggle to find a way to write creatively to express her grief, and unexpected happy experiences when Margaret uses writing as proof that she has overcome grief with all her might.